Edukasi Makanan Sehat dengan Permainan Puzzle di SDN 005 Km.2 Pekan Heran Kabupaten Indragiri Hulu - Julita, Sety (PITIMAS: Journal of Community Engagement in Health, 2024)
Healthy food education activities at SDN 005 KM 2 Pekan Heran with a focus on the background, objectives and conclusions regarding healthy food. The background of healthy food is a major concern amidst increasing health problems for children, such as obesity and a lack of understanding of the importance of balanced nutrition. The main aim of this activity is to increase students' understanding of healthy food through health games in the form of fruit and vegetable puzzles. Over three days, we engaged students in interactive health games, where they actively participated in assembling fruit and vegetable puzzles. This activity begins with a pre-test to measure students' initial level of understanding regarding healthy food. The pre-test results showed that 66.6% of students did not fully understand the concept of healthy food. After three days of activities, a post-test was carried out to evaluate the effectiveness of the activities. The post-test results showed a significant increase, with students' understanding level reaching 86.6%. This shows that health games in the form of fruit and vegetable puzzles can effectively increase students' knowledge about healthy food. The conclusion from this activity is that an interactive and play approach can be an effective means of conveying information about healthy food to students at SDN 005 KM 2 Pekan Heran. By involving students in health games, it can be hoped that their awareness of the importance of healthy food will increase, contributing to the formation of a healthy lifestyle from an early age.